Environment-dependent chlorophyll–chlorophyll charge transfer states in Lhca4 pigment–protein complex - Rankelytė, Gabrielė; Gelzinis, Andrius; Robert, Bruno; Valkunas, Leonas; Chmeliov, Jevgenij (Frontiers in Plant Science, 2024)
Photosystem I (PSI) light-harvesting antenna complexes LHCI contain spectral forms that absorb and emit photons of lower energy than that of its primary electron donor, P700. The most red-shifted fluorescence is associated with the Lhca4 complex. It has been suggested that this red emission is related to the inter-chlorophyll charge transfer (CT) states. In this work we present a systematic quantum-chemical study of the CT states in Lhca4, accounting for the influence of the protein environment by estimating the electrostatic interactions. We show that significant energy shifts result from these interactions and propose that the emission of the Lhca4 complex is related not only to the previously proposed a603+–a608− state, but also to the a602+–a603− state. We also investigate how different protonation patterns of protein amino acids affect the energetics of the CT states.